In-Service Teacher Training for Professional Development: Voices from Secondary Level English Teachers - Kshetree, Arun Kumar; Jyoti, Rameshwar (BMC Research Journal, 2025)
In-service teacher training is a structured programme designed to help teachers refresh and enhance their professional knowledge, skills, and practices. This study aimed to explore the perceptions of secondary level in-service English teachers on the appositeness of in-service teacher training for professional development. We employed a narrative inquiry design. For our research participants, we purposively selected three (two male and one female) secondary level English teachers teaching in three different community schools in Rupandehi district for more than seven years. They were interviewed using semi-structured in-depth interview techniques to elicit the data. After transcribing and coding the data, they were analysed under the themes created. The study revealed that teachers were positive toward in-service teacher training. They viewed that in-service teacher training supported them to grow professionally with innovative knowledge, skills, and methods. However, they often found it difficult to apply the knowledge, skills, and practices they acquired in the training sessions in their classroom contexts. Further, they emphasized the need for regular, need-based, and ICT-focused training. Besides, they expressed that there was a mismatch between teachers’ expectations from the training and what they learned in the training hall. This study contributes to the understanding of in-service teachers and other stakeholders about the suitability and challenges teachers face in applying the knowledge learned from the training in real classroom situations. The study has opened a venue for further research to be carried out on how teacher training impacts student performance.